2020
DOI: 10.1097/jxx.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Exploring family nurse practitioner professional identity formation at rural health care facilities

Abstract: Background: Nurse practitioners (NPs) are being used to meet the increased demand for rural primary care. Purpose: The purpose of this study was to explore the perceptions and experiences of rural NPs while they transitioned from being registered nurses to family NPs (FNPs). In addition, the study examined if and how new FNPs experienced their professional identity formation in their first year of rural primary care practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Recent research discovered that a variety of competitive pay and benefits policies promote nurse intent to stay, recruitment, and work satisfaction. 3,5,20 Findings for this current study were similar; however, the present study adds to research gaps since its sample included practicing nurses at all practice and educa-tion levels and soon-to-graduate nursing students at a variety of education levels.…”
Section: Qualitative Datasupporting
confidence: 55%
See 2 more Smart Citations
“…Recent research discovered that a variety of competitive pay and benefits policies promote nurse intent to stay, recruitment, and work satisfaction. 3,5,20 Findings for this current study were similar; however, the present study adds to research gaps since its sample included practicing nurses at all practice and educa-tion levels and soon-to-graduate nursing students at a variety of education levels.…”
Section: Qualitative Datasupporting
confidence: 55%
“…4 Another recent study found comparable results for NPs. 5 In addition, allowing NPs to practice within their full scope of practice was important to NP's work satisfaction and intent to stay. 5 Incivility negatively impacts the work environment by having a detrimental effect on individuals, teams, organizations, and patient safety, and is a major reason why nurses leave their positions.…”
Section: Current State Of Nurse Work Environment Work Satisfaction An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Global Strategic directions for nursing and midwifery 2021–2025 [ 47 ] provides policy priorities, aligned with the guidance above, to ensure that nurses maximally contribute to national health goals and UHC. Policy-relevant evidence on what specifically contributes to nurses’ retention in health and care settings [ 48 51 ], including for advanced practice nurses in rural and remote settings, is increasingly available [ 52 54 ]. Institutionalizing these aspects requires a context-specific aligning of the education, training, and lifelong learning of nurses with optimized roles of nurse in the health system, updating and strengthening professional regulations, providing leadership and career advancement opportunities, ensuring safe and supportive service delivery environments, and competent management, planning and forecasting of the nursing workforce to ensure nurses are where they are most needed [ 31 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the social identity theory, identity can influence individual thinking, emotion and behaviour (Liu et al, 2021); therefore, professional identity will inevitably have an impact on the nursing practice (Shun, 2021). Nurses with a higher professional identity have a stronger sense of professional benefit, and can experience more pride, efficacy, achievement and happiness at work; therefore, their work enthusiasm and caring ability are higher (Luo et al, 2018; Owens, 2020). On the contrary, nurses with low professional identity will tend to exhibit negative attitudes and behaviours at work and reduce their sense of belonging, and then reduce their work engagement when they perceive that their self‐worth is not reflected in work and that their profession is not recognized by the society (Wang, Hu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%